12-Month color stability of enamel, dentine, and enamel-dentine samples after bleaching - Wiegand, Annette; Drebenstedt, Steffi; Roos, Malgorzata; Magalhaes, Ana Carolina [UNESP]; Attin, Thomas (Springer Heidelberg, 2008)
The study aimed to quantify the color regression of enamel (E), dentine (D), and combined enamel-dentine (ED) of differently bleached ED specimens over a period of 12 months in vitro. Two ED samples were obtained from the labial surfaces of bovine teeth and prepared to a standardized thickness with the enamel and dentine layer each 1 mm. The ED samples were distributed on four groups (each n=80), in which the different bleaching products were applied on enamel (1, Whitestrips; 2, Illumine 15%; 3, Opalescence Xtra Boost) or dentine surfaces (4, mixture of sodium perborate/distilled water). Eighty ED samples were not bleached (control). Color (L*a*b*) of ED was assessed at baseline, subsequently after bleaching and at 3, 6, and 12 months of storage after bleaching (each 20 samples/group). E and D samples were prepared by removing the dentine or enamel layer of ED samples to allow for separate color analysis. Bleaching resulted in a significant color change (Delta E) of ED specimens. Within the observation period, Delta L but not Delta b declined to baseline. L* values of E and D samples also declined and were not significantly different from control samples after 12 months, while b* values did not decrease to baseline. Generally, no differences between the bleaching agents could be observed. Color change of enamel, dentine, and combined ED of in vitro bleached tooth samples is not stable over time with regard to lightness. However, yellowness did not return to baseline within 1 year.
Keywords: Bleaching; Color; Enamel; Dentine